Goals and Aspirations of Nursing and Midwifery Students at the End of the Degree, at the University of Guanajuato Campus Irapuato – Salamanca (Jóvenes en la Ciencia, 2024)
Various studies have shown that university students perceive uncertainty about finding a job when they finish their studies, in addition there is no satisfaction with the remuneration at the work level, so students prefer to study a postgraduate degree, some other career and even emigrate to another country in order to achieve a better future. However, to date there is a great deal of controversy about the plans that university students have once they conclude their studies. In this sense, the objective of this project was to analyze the different goals and aspirations of the students of the Nursing and Midwifery career of 6th and 8th semester of the University of Guanajuato, Irapuato-Salamanca Campus. A quantitative, descriptive and cross-sectional study was carried out through a Merkel survey of a total of 105 students of the Department of Nursing and Midwifery. It was found that in 87.2% of the students the motivation arose naturally, the majority with 46.67% considered it as their first choice of study, 95.4% plan to continue with the career professionally, 40% referred to a good sense of vocation of the career and 39.05% referred a lot, in satisfaction, the majority with 57.14% felt quite satisfied in the choice of the career. These results suggest that the outlook of the majority of university students for the future is optimistic, most of them seek the professional continuity of their knowledge and their approach is based on the specialization and continuous development of their skills and competencies in the area of health, mostly at the second level of care at the national level.